Composition and biological effects of goldenberry byproducts: an overview. (18th May 2020) - Nocetti, Diego; Núñez, Hipólito; Puente, Luis; Espinosa, Alejandra; Romero, Fernando
Abstract: Goldenberry is a wild fruit that has been widely used for centuries, mainly in folk medicine. Most studies of goldenberry have focused on the fruit, but new research has studied its byproducts, which were considered to be waste until recently. The main objective of our study was to systematize the published information regarding the composition of goldenberry byproducts (calyces, leaves, seeds, and pomace) and their effects on biological systems. Goldenberry byproducts contain minerals, amino acids, withanolides, flavonoids, and essential fatty acids, thus representing good sources of these compounds. Some of their major biological effects include anti‐inflammatory, antioxidant, antidiabetic, and antiproliferative effects. Information regarding their toxicity is also presented here. To determine the optimal dosage, further safety studies would be recommended to ensure the best health benefits of these compounds. The available evidence has demonstrated the nutritional value of different byproducts of goldenberry, suggesting them to be potential candidates for use in the cosmetic industry, in the preparation of functional foods, and in phytomedicine for the prevention and adjuvant treatment of some diseases. © 2020 Society of Chemical Industry